2020
DOI: 10.1016/j.heliyon.2019.e03088
|View full text |Cite
|
Sign up to set email alerts
|

How suspended solids concentration affects nitrification rate in microalgal-bacterial photobioreactors without external aeration

Abstract: The use of microalgae for the treatment of municipal wastewater makes possible to supply oxygen and save energy, but must be coupled with bacterial nitrification to obtain nitrogen removal efficiency above 90%. This paper explores how the concentration of Total Suspended Solids (TSS, from 0.2 to 3.9 g TSS/L) affects the nitrification kinetic in three microalgal-bacterial consortia treating real municipal wastewater. Two different behaviors were observed: (1) solid-limited kinetic at low TSS concentrations, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The photosynthesis process would also synthesize the new biomass of phytoplankton. As water column productivity increased, the growth from microorganisms would then consume ions from the treated IMTA water [15,16,17]. This biomass production was also related to the dynamics of turbidity in the WSP pond.…”
Section: Resultsmentioning
confidence: 99%
“…The photosynthesis process would also synthesize the new biomass of phytoplankton. As water column productivity increased, the growth from microorganisms would then consume ions from the treated IMTA water [15,16,17]. This biomass production was also related to the dynamics of turbidity in the WSP pond.…”
Section: Resultsmentioning
confidence: 99%
“…There were many possible reasons for this phenomenon, algae feeding, the algae's growth and reproduction, as well as the feed residue all would raise the TSS (Mark et al, 2018). Besides, bioflocs provided the growth environment for microalgae in the BFT system, indicating that a certain concentration of TSS could better maintain the abundance of microalgae (Foladori et al, 2020). T600 showed the fastest decrease in microalgae when feeding microalgae was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the photo-oxygen generated by algal biomass is sufficient enough for heterotrophic bacterial oxidation of organic matter under no-aeration conditions, and satisfactory carbon removal has been achieved [ 154 , 155 ]. However, contradicting this observation, other researchers have shown that the addition of external aeration improves the removal efficiency [ 54 ].…”
Section: Physio-chemical Factors Affecting Algal-bacterial Systemsmentioning
confidence: 99%